STRATEGI PENGEMBANGAN USAHA KERUPUK RAMBAK KULIT IKAN KERAPU DI DESA SUNGEGENENG KECAMATAN SEKARAN KABUPATEN LAMONGAN - Ristyanadi, Bhiaztika; Pratiwi, Yora Utami Putri; Andriawan, Achmad Rizal Dwi (Jurnal Perikanan Unram, 2025)
One of the businesses that has great opportunities in Lamongan Regency is processed grouper skin rambak crackers. One of the processing areas for fish skin crackers in the Lamongan area is in Sungegeneng Village, Sekaran District. The large amount of waste from grouper handling factories has provided business opportunities to process grouper skin waste into rambak crackers. The realization of the grouper skin cracker processing business is still not growing rapidly, so input is needed to find a business development strategy. The purpose of this study is to find out the characteristics of business actors and business profiles as well as identify internal and external factors that affect business development and then formulate strategies that can be applied in the development of fish skin cracker business. The method used in this study is a qualitative descriptive method with a case study approach and the case unit is the processing of grouper fish skin crackers in Sungegeneng Village, Sekaran District, Lamongan Regency. The results of the analysis in the SWOT matrix obtained the coordinates (0.767; 1,210) which is located in quadrant I (one) or growth conditions, namely the SO strategy (strenght and opportunities) that supports aggressive growth policies. The strategy that can be applied is to maintain product quality by choosing raw materials that are still fresh and processing grouper fish skins properly in accordance with Good Fish Processing Practices (CPIB), improving more modern processing technology by using adequate drying technology to meet large market demand, improving the bookkeeping system, and utilizing government support in marketing products and capacity building through training Digital Marketing organized by related stakeholders.